Three AP2/ERF family members modulate flavonoid synthesis by regulating type IV chalcone isomerase in citrus. Issue 4 (27th November 2020) - Zhao, Chenning; Liu, Xiaojuan; Gong, Qin; Cao, Jinping; Shen, Wanxia; Yin, Xueren; Grierson, Donald; Zhang, Bo; Xu, Changjie; Li, Xian; Chen, Kunsong; Sun, Chongde
Summary: Flavanones and flavones are excellent source of bioactive compounds but the molecular basis of their highly efficient production remains elusive. Chalcone isomerase (CHI) family proteins play essential roles in flavonoid biosynthesis but little are known about the transcription factors controlling their gene expression. Here, we identified a type IV CHI (designated as CitCHIL1) from citrus which enhances the accumulation of citrus flavanones and flavones (CFLs). CitCHIL1 participates in a CFL biosynthetic metabolon and assists the cyclization of naringenin chalcone to ( 2S )‐naringenin, which leads to the efficient influx of substrates to chalcone synthase (CHS) and improves the catalytic efficiency of CHS. Overexpressing CitCHIL1 in Citrus and Arabidopsis significantly increased flavonoid content and RNA interference‐induced silencing of CitCHIL1 in citrus led to a 43% reduction in CFL content. Three AP2/ERF transcription factors were identified as positive regulators of the CitCHIL1 expression. Of these, two dehydration‐responsive element binding (DREB) proteins, CitERF32 and CitERF33, activated the transcription by directly binding to the CGCCGC motif in the promoter, while CitRAV1 (RAV: related to ABI3/VP1) formed a transcription complex with CitERF33 that strongly enhanced the activation efficiency and flavonoid accumulation. These results not only illustrate the specific function that CitCHIL1 executes in CFL biosynthesis but also reveal a new DREB‐RAV transcriptional complex regulating flavonoid production.